Cultural mapping of TQM. - Kong, Benson Yew Hong. (2008)
In this research, we are looking into one of the many suggested hurdles of TQM. We are finding out whether the culture of Singapore may be a cause of slow growth to the implementation of this management style. We carried out a questionnaire survey to tap into the views of future and current employees. The questionnaire is structured in a way that will enable us to map the Singapore culture to the TQM culture. The questionnaire is structured in the viewpoint of TQM.